[μ-1,6-Bis(diphenylarsanyl)hexane]bis[chloridogold(I)] - Shawkataly, Omar bin (International Union of Crystallography, 2011)
In the title compound, [Au(2)Cl(2)(C(30)H(32)As(2))], each Au atom is coordinated by As and Cl atoms in an approximately linear geometry. In the crystal, molecules are linked into two-dimensional networks parallel to the ac plane via intermolecular C—H⋯Cl interactions. One of the phenyl rings is disordered over two positions, with site occupancies of 0.518 (8) and 0.482 (8).